Manajemen Sekolah Mewujudkan Prestasi Pramuka Garuda di SMP Negeri I Saptosari Gunungkidul - Nugroho, Agung; Rejokirono, Rejokirono (Universitas Sarjanawiyata Tamansiswa, 2025)
Education has an important role in forming a generation that has good character, ethics and morals. The important role of education in forming a generation of character is the main goal of education. Scout education is an effective program in improving character, developing leadership, moral ethics, personality formation, independence, self-confidence, and achieving student achievement. Scouting is one of the extracurricular education that can be implemented. This research explores how school management at SMP Negeri 1 Saptosari can improve student achievement and discipline through Scouting. The achievement that can be achieved from Scouting is becoming a Garuda Scout. Garuda Scouting is achieved through various tests so that students will obtain the highest Garuda Scout/Scout title. Using a qualitative case study method, the research involved interviews, observation, and document analysis. The results show that good management can make Scouting a superior program that can improve student achievement in achieving the Garuda Scout title, as well as having a big impact on the development of education at SMP Negeri I Saptosari.